Case report: A novel FBXW7 gene variant causes global developmental delay - Wang, Yu; Ma, Xiaoping; Li, Hua; Dai, Yanrui; Wang, Xiaochen; Liu, Li (Frontiers in Genetics, 2024)
OBJECTIVE: To investigate a case of neurodevelopmental disorder caused by mutation of FBXW7. METHODS: Clinical data were collected from the patient, trio-WES (whole-exome sequencing) was performed on the patient and his parents (trio), and the results were verified by Sanger sequencing. RESULTS: The patient was a two-year and one-month old male who presented with facial dysmorphism (prominent forehead, ocular hypertelorism, and low nasal bridge), global developmental delay, language impairment, hypertonia, labial hemangioma, hydrocele, and overgrowth. The trio-WES confirmed that the child had a pathogenic de novo FBXW7 gene variant, c.1612C>T (p.G1n538*), a heretofore unreported locus. CONCLUSIONS: This case of developmental delay, hypotonia, and impaired language (OMIM: #620012) related to a mutation in FBXW7, is a rare genetic disorder, newly identified in recent years, and seldom reported. The presence of hypertonia, labial hemangioma, and hydrocele in this child suggests significant phenotypic heterogeneity of the disease, and the discovery of new mutant loci enriches the spectrum of pathogenic variants of the disease.